2021
DOI: 10.1186/s40814-021-00825-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of non-invasive, individualized, transcranial neuromodulation treatment for voiding dysfunction in multiple sclerosis patients: study protocol for a pilot clinical trial

Abstract: Background Voiding dysfunction (VD) is a common neurogenic lower urinary tract dysfunction (NLUTD) in multiple sclerosis (MS) patients. Currently, the only effective management for VD and urinary retention in MS patients is catheterization, prompting us to look for novel therapeutic options beyond the bladder, such as the brain. Transcranial rotating permanent magnet stimulator (TRPMS) is a non-invasive, portable, multifocal neuromodulator that simultaneously modulates multiple cortical regions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Patients with MS experience adverse conditions, such as sleep disturbance, fatigue, urinary tract infection, low self-esteem, and mood disorders due to lower urinary system dysfunction. Studies have reported that the recommended treatment should have the least side effects ( 22 ). For this reason, we searched for neuromodulation methods that were reported to have the least side effects in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MS experience adverse conditions, such as sleep disturbance, fatigue, urinary tract infection, low self-esteem, and mood disorders due to lower urinary system dysfunction. Studies have reported that the recommended treatment should have the least side effects ( 22 ). For this reason, we searched for neuromodulation methods that were reported to have the least side effects in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and functional MRI images were collected per our previous protocol. 9 During the concurrent functional magnetic resonance imaging (fMRI)/UDS, the bladder was filled with sterile saline at 75 ml/minute until subjects signaled a “strong desire to void.” Subjects were instructed to hold for 30 seconds, after which permission to void was given. UDS was performed concurrently during fMRI to monitor the entire filling and voiding cycles.…”
Section: Methodsmentioning
confidence: 99%
“…Validated questionnaires, noninstrumented uroflow, and PVR volume were collected for inclusion criteria and as baseline values, and again at post-treatment, and 4-month and 12-month followups. 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient dropped out due to COVID‐19 and one patient was excluded from analysis because of a significant loss of brain tissue found during the magnetic resonance imaging (MRI) scanning. Ten healthy women and nine MS women were included for the analysis 4,10 . Patients with prior slings, bladder/bladder neck suspension operations, or previous bladder reconstruction procedures were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%